Pengaruh pemberian silase limbah ikan dalam ransum nabati terhadap performa ayam Broiler - Lisnawaty Silitonga; Robertho Imanuel; Hesti Anggraeni (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
This research aimed to know the effect of silage fish waste in vegetable feed to performance of that broiler. This research used completely Randomized Design (CRD) with four treatments that is P0 (Control Feed Treatment), P1 (Treatment Feed 95% + 5% Silage Of Waste Fish), P2 (Treatment Feed 90% + 10% Silage Of Fish Waste), P3 (Treatment Feed 85% + 15% Silage Of Fish Waste), and five replications. The results showed that the silase fish waste had significant effect to weight gain and weight carcass (P>0,05), had significant effect to consumption (P 0,05). The highest body weight gain and feed consumption was gave level 15% silage of fish. Keywords : Fish waste silage, broiler, performance, and carcass weight.